Pengembangan Instrumen Evaluasi Domain Afektif - Rohmad Qomari (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
To carry out evaluation comprehensively, we need appropriate instrument that suitable with domain that being evaluated. Evaluation instrument development with test has been conducted by experts. These instruments were only suitable to measure cognitive domain and part of psychomotor domain. To measure affective domain, we need to develop non-test evaluation instrument (alternative test). The development of this instrument tends to more difficult and complicated compare with instrument test evaluation instrument. Therefore, it does necessitate a through study to derive and elaborate affective domain to specific aspect to develop valid and reliable instrument.